Differential expression of TGF-β and IL-1R2 genes during endometritis infection in Egyptian buffalo - OTHMAN E OTHMAN; DALIA M MABROUK; HEBA A ABD EL-KADER; SALLY A ALAM; SEKINA H ABD EL-AZIEM (Indian Journal of Animal Sciences, 2020)
Contamination of the uterine lumen with bacteria occurred in bovid within the first week after parturition. The bacterial infection causes the persistent inflammation in the endometrium leading to the infertility and huge economical loss in animal production. TGF-β and IL-1R2 genes are involved in innate immune recognition of pathogens and the inflammatory response. This study aimed to compare the expression of these two genes in uteri samples of endometritis-infected and apparently healthy buffaloes using QT-PCR. The uteri samples were collected from endometritis-infected and normal buffaloes. Bacterial examination of uteri from endometritis-infected buffaloes showed the presence of bacterial contamination with E. coli, P. Klebsiella pneumonia and/or P. vulgaris. RNA was extracted from uteri of infected and normal animal, and cDNA was synthesized for QT-PCR. Using GAPDH as a housekeeping gene, the gene expression of two tested genes was assessed and the results showed that the expression of TGF-β and IL-1R2 genes was up-regulated in infected animals compared to control by 11.39 and 12.99 folds, respectively and this increase of gene expressions was highly significant. In conclusion, the gene expression assessment of important innate immune genes—like TGF-β and IL-1R2 genes can help to establish new approaches for the improvement of the immune response of buffalo through marker-assisted selection of animals characterized by superior innate immunity system.